The Effect of Profitability and Capital Structure on Firm Value with Dividends as a Moderating Variable (Case Study of Companies Listed on the LQ-45 Index for the 2018-2021 Period) - Sugiyanto Sugiyanto; Imronudin Imronudin; Moechammad Nasir; Ma’rifah Ma’rifah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The purpose of this study is to test whether (1) profitability has a positive effect on company value. (2) The capital structure of the company has a positive effect on its value. (3) the positive effect of profitability on company value through a dividend policy. (4) the positive influence of capital structure on company value through dividend policy. The population in this study are companies listed in the LQ-45 Index for the period 2018–2021. As for the samples to be tested, namely those from companies listed on the LQ-45 Index, as many as 92 research samples from 23 companies were collected. The analysis methods used for this study are: variable descriptive statistical testing; panel data regression analysis with a common effects model (CEM) approach; fixed effect modeling (FEM); random effect modeling (REM); the R2 coefficient of determination; the F test; the T test; the normality test; and the moderation test. (1) Profitability (X1) partially has no significant effect on company value at LQ-45 in 2018–2021. (2) Partial capital structure (X2) has no significant effect on company value at LQ-45 in 2018–2021. (3) The dividend payout ratio is significant as a moderator of the relationship between profitability (ROE) and company value at LQ-45 in 2018–2021. (4) The dividend payout ratio is not significant as a moderator of the relationship between capital structure (DER) and company value at Lq-45 in 2018-2021.